The Analysis Main and Differential Dissipation of The Inductances Windings Stator an Energy Method - Mustafakulova Gulzoda Narkabilovna; Askarov Elmurod Pulatzhan ugli (Zien Journals, 2021)
In article are brought methods of the calculation main and differential dissipation of the inductances, which allows to take into account all factors, influencing upon inductances, except influences of unevenness of the air clearance between steel still part and rotor and демпфирующего influences current, directed in secondary sidebar by fields high spatial harmonic, created by winding статора machines of alternating current. The Proposed methods of the calculation is founded on models of the field of the air clearance of the electric machine of alternating current.
Keywords: Differential dissipation of the inductances; steel still part; air clearance; energy and harmonic analysis